Antioxidant and Antitumor Activities of the Extracts from Chinese Yam (Dioscorea opposite Thunb.) Flesh and Peel and the Effective Compounds. Issue 6 (27th April 2016) - Liu, Yuanxue; Li, Hongfa; Fan, Yaya; Man, Shuli; Liu, Zhen; Gao, Wenyuan; Wang, Tingting
Abstract: The aims of this study are to investigate the antioxidant and antitumor activities of the water and ethanol extracts isolated from Chinese yam (Dioscorea opposite Thunb.) flesh (CYF) and peel (CYP) and the effective compounds. It was found that all peel portions have a better effect on reactive oxygen (ROS) scavenging assay than meat portions, especially for the water extract of Chinese yam peel (CYP‐W). Its IC50 values for hydroxyl radical (OH) scavenging assay (744.25 ± 3.46 μg/mL) and for 1, 1‐diphenyl‐2‐picrylhydrazyl scavenging assay (374.85 ± 6.78 μg/mL) were both lower than that of yam flesh (CYF‐W). Furthermore, the antitumor property of yam peel was more effective than that of yam flesh (CYF‐W) on mouse models, with tumor inhibition rates were 47.92% and 27.41% for Ehrlich Ascites Tumor (EAC) model and 40.44% and 24.22% for H22 hepatocarcinoma tumor (H22) model. Meanwhile, extracts of peel showed higher allantoin, total flavonoids, and total phenolics contents than extracts of flesh. In conclusion, this study demonstrated that CYP‐W exerted better antitumor activity than flesh extracts and the scavenging ROS effects were also significantly higher in the CYP‐W in vitro . Moreover, the data indicated that allantoin may play an important role on antioxidative and antitumor capacity in yam peel.